A Multiple Perspectives Analysis of the Influences on the School to Prison Pipeline in Virginia, 2013-2015 - Lawson, Gerard ([Verlag nicht ermittelbar], 2020)
This study consists of both qualitative and quantitative investigation of the influences on the school to prison pipeline. The quantitative study, the one included in this release, brings together four large datasets maintained by the Virginia Department of Education (DOE; Discipline Crime and Violence [DCV]), Department of Criminal Justice Services (DCJS; School Safety Audits and School Climate Data), and Department of Juvenile Justice (DJJ; Juvenile Referrals and Intakes). These datasets were used to compare what characteristics (individual or building level) either increase or decrease the odds that a student will become involved with the criminal justice system, as a result of school behaviors. The qualitative study involved in-depth individual interviews with 34 educational stakeholders across Virginia, who are involved in the discipline process in the schools (e.g. administrators, counselors, School Resource Officers). The analysis of these interviews found that the themes in how school discipline is differentiated from law enforcement in the schools, and the efforts that schools communities are making to keep children in the classroom and out of the courtroom. Individuals are the unit of analysis. The sample includes the following vulnerable populations: children, minorities, institutionalized persons, and persons with disabilities.